Students Perceptions of Learning Biology at SMA Negeri 1 Binjai - Zahra, Maurin; Ulfa, Syarifah Widya; Jayanti, Ummi Nur Afinni Dwi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study aims to identify students' perceptions of learning biology at SMA Negeri 1 Binjai Kab. Langkat. This research is directed at learning that takes place at the school and classes X-IPA, XI-IPA and XII-IPA as research samples. This study uses a survey method. Sampling is by means of probability random sampling in the form of proportionate stratified random sampling. because the study population was divided into several strata or sub-groups and separate samples were taken from each sub-group. The number of respondents obtained is 123 students. The instrument used is a questionnaire that has been prepared in such a way and has been validated previously. The results of the analysis show that students' perceptions of biology learning on average show negative results. So the student's perception of learning biology at SMA Negeri 1 Binjai Kab. Langkat is in the unfavorable category. Some of the things that influence students' perceptions of learning biology at SMA Negeri 1 Binjai Kab. Langkat are internal and external factors. Internal factors include students' learning abilities, motivation towards biology lessons and the ability to develop a knowledge. While external factors include the strategies used, learning media and physical conditions that support learning when it is in progress.